Lymphoscintigraphic Findings as Indicators of Lymphaticovenous Anastomosis Outcome in Patients With Extremity Lymphedema: A Retrospective Cohort Study. (July 2021) - Kim, Hye Ok; Woo, Kyong-Je; Kim, Bom Sahn; Kang, Seo Young; Moon, Byung Seok; Yoon, Hai-Jeon
Abstract : Purpose: This study was performed to evaluate the usefulness of lymphoscintigraphy in predicting the surgical outcomes of lymphaticovenous anastomosis (LVA) in a patient with extremity lymphedema. Patients and Methods: We retrospectively evaluated 133 patients with extremity lymphedema who underwent lymphoscintigraphy followed by LVA surgery from February 2018 to March 2020. Lymphoscintigraphic findings were evaluated on the following parameters: the extent of dermal backflow (small/large), lymphatic flow patterns (trunk flow pattern/proximal-restricted pattern/distal-restricted pattern), visualization of lymph nodes, and collateral lymphatic vessels. The mean circumferential difference change before and after surgery, circumferential reduction (CR) rate (%), was used as the clinical outcome variables. Results: A decrease in circumference was observed in 93 (69.9%) of 133 patients after LVA. The extent of dermal backflow and lymphatic flow patterns was significantly correlated with improved clinical outcomes after LVA. The large extent of the dermal backflow group showed a more significant CR rate than the small extent (19.27% vs 1.24%, P = 0.005). The TP group showed the most significantly decreased CR rate to 21.46%, and the proximal-restricted pattern and distal-restricted pattern groups were −2.49% and −5.33%, respectively ( P < 0.001). Multivariate analysis revealed that dermal backflow and lymphatic flow patterns were independent predictors of therapeutic outcome ( P < 0.001). Conclusions: Our study demonstrates that pretreatment lymphoscintigraphy may help predict the therapeutic effect of LVA in patients with extremity lymphedema. Furthermore, dermal backflow and lymphatic flow patterns are independent predictors of CR rate after LVA surgery for extremity lymphedema.